Iskemia Tungkai Akut: Perspektif Baru pada Diagnosis, Pengobatan, dan Upaya Pencegahan Amputasi - Balqis, Fathinnisa Adillah; Ermawan, Romi; Nugraha, Gede Rama Hardy; Ragad, Putra; Dewi, Komang Puspa; Ramadhani, Dhea Asty; Rizky, Muhammad Ilham (TRILOGI: Jurnal Ilmu Teknologi, Kesehatan, dan Humaniora, 2024)
Acute Limb Ischemia (ALI) is a medical emergency caused by a sudden decrease in blood flow to the extremities, often within less than two weeks. This review examines the definition, epidemiology, pathophysiology, clinical presentation, and management of ALI. The condition is primarily triggered by thrombosis or embolism in arteries previously affected by atherosclerosis. Characteristic symptoms include the "6 Ps": pain, paresthesia, poikilothermia, paralysis, pulselessness, and pallor. Diagnosis involves a combination of medical history, physical examination, and imaging, particularly Doppler ultrasound. Management strategies focus on prompt revascularization using catheter-directed thrombolysis, open embolectomy, or percutaneous mechanical thrombectomy. The Rutherford classification is employed to assess severity and guide treatment plans. Timely and effective intervention significantly improves patient outcomes, minimizes the risk of major amputation, and preserves limb function. This study emphasizes the importance of multidisciplinary collaboration in ALI management to optimize prognosis.